Infiltration Capacity and Structural Analysis of Permeable Pavements for Sustainable Urban: A Full-scale Case Study. (15th March 2021) - Liu, Quan; Liu, Sufang; Hu, Gaohui; Yang, Tao; Du, Cong; Oeser, Markus
Abstract: For sustainable urban development, the permeable pavement aggressively attracts interests to promote urban water management. This study compared the infiltration and bearing capacities of different permeable pavement structures. To this end, artificial rainfalls with five different intensities were performed on four full-size pavement structures. The infiltration capacity of permeable pavements was estimated based on the runoff curves derived from in-situ measurement. Moreover, their clogging resistance capacity and recovery capacity after maintenance were featured respectively. The Finite Element Method (FEM) was conducted to compare the bearing capacity of four investigated pavement structures. The laboratory results demonstrated the permeability of asphalt mixtures was highly dependent on the water head difference. With regard to the field investigation, it was found that a thicker pavement structure enlarged the infiltration distance, as a result, extending the runoff rising moment and decreasing moment. Besides, a thicker pavement structure can effectively decrease the maximum runoff flow. Furthermore, a reasonable air void combination of multi layers is critical to achieve the optimal permeable performance of the pavement. Multi-layer structure pavement showed superior resistance to the clogging and recovery capacity under maintenance due to the existence of a clogging buffer area.